2014
DOI: 10.1634/theoncologist.2014-0152
|View full text |Cite
|
Sign up to set email alerts
|

Low Socioeconomic Status Is Associated With More Aggressive End-of-Life Care for Working-Age Terminal Cancer Patients

Abstract: Background. The relationship between low socioeconomic status (SES) and aggressiveness of end-of-life (EOL) care in cancer patients of working age (older than 18 years and younger than 65 years) is not clear.We assessed the association between aggressiveness of EOL care and differences in SES among working-age terminal cancer patients from Taiwan between 2009 and 2011. Methods. A total of 32,800 cancer deaths were identified from the Taiwan National Health Insurance Research Database. The indicators of aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Diagnosis status was divided into three subgroups of cancers that were homogeneous in terms of survival and disease course [18][19][20]. Patients with nonmetastatic cancer and hematologic malignancies were excluded from this study.…”
Section: Databasementioning
confidence: 99%
“…Diagnosis status was divided into three subgroups of cancers that were homogeneous in terms of survival and disease course [18][19][20]. Patients with nonmetastatic cancer and hematologic malignancies were excluded from this study.…”
Section: Databasementioning
confidence: 99%
“…Statistics Belgium also manages the national demographic database, derived from the population register [ 16 ] and containing for example the household composition of every citizen and data from the Socio-Economic Survey 2001 and Census 2011, nationwide full population surveys based on the tradition of population count [ 17 ]. The database contains information about the highest educational level attained, the last held occupation (as a measure of socio-economic position) and housing characteristics, which are all socio-economic factors that have been identified in previous studies as affecting end-of-life care patterns [ 18 20 ]. Finally a database containing fiscal data (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This result was dissimilar to the result of a study in Taiwan. The previous study found that patients with low socioeconomic status, have metastatic malignant disease, residing in urban areas or are in hospitals with more abundant health care resources are likely to receive aggressive end-oflife care to delay death [18]. However, one American study reported that patients living in low-income zip codes are less likely to receive aggressive end-of-life cancer treatment than patients living in other zip codes [19].…”
Section: Predictors Of Preferring Receiving Appropriate Palliative Carementioning
confidence: 99%